The Effects and the Effectiveness of the Functioning of the International Criminal Court - Munivrana, Maja (The ICC at 25: Lessons Learnt, 2025)
The Rome Statute of the International Criminal Court (hereinafter: the ICC) was adopted in 1998 and entered into force in 2002, marking the establishment of the ICC. Quarter of a century later and more than two decades since the ICC became operational, sufficient time has passed to undertake a comprehensive assessment of its performance - evaluating both its achievements and shortcomings, as well as the lessons learned along the way. In recent years, a range of actors—including scholars, expert bodies, non-governmental organizations, and the ICC itself—have conducted various assessmentsof the Court’s work. After a brief introductory mapping of these different assessments, the central part of the paper deals with a methodological dilemma of choosing the right metrics. The paper identifies several evaluative approaches frequently referenced in academic literature and policy discourse, but also others that, while less commonly employed, merit inclusion in any serious discussion about the Court's effectiveness. In turn, it explores quantitative approach focused on empirical data, goal-oriented analysiswith special emphasis on deterrence, assessment grounded in gender justice considerations and finally evaluations that take into account post-trial (in)justices. By examining these varied methodologies, the paper reveals the inherent complexities and limitations of measuring the ICC’s effectiveness. These difficulties are then zoomed in in the last part of the paper which critically reflects on the challenges and promises of looking at the ICC effectiveness through different possible lenses. Keywords: the ICC, effectiveness, metrics, goals, deterrence, gender justice, post-trial justice